2018
DOI: 10.2478/jwld-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on the water requirements of the Bounamoussa perimeter, North-East of Algeria

Abstract: The objective of this work is to determine the effects of climate change on the water needs of crops in the Bounamoussa perimeter, which is one of the large irrigation systems in the North-East of Algeria in order to predict a diagnosis of its operation. This region covers an area of 16,500 ha and is specialized in vegetable production.The climatic trend of recent years in the study area is characterized by increasingly severe drought conditions that have compromised agricultural production at this perimeter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Fresh vegetables and fruits will continue to breathe despite being separated from their regular nutritional sources and the parent plant (Malkia & Etsouri, 2018). A product's rate of respiration can be assessed by either the rate of CO 2 generation or the rate of O 2 absorption under typical aerobic circumstances.…”
Section: Applications Of Mapmentioning
confidence: 99%
“…Fresh vegetables and fruits will continue to breathe despite being separated from their regular nutritional sources and the parent plant (Malkia & Etsouri, 2018). A product's rate of respiration can be assessed by either the rate of CO 2 generation or the rate of O 2 absorption under typical aerobic circumstances.…”
Section: Applications Of Mapmentioning
confidence: 99%
“…Changes in crop water requirements with climate change have been observed in many countries in the basin. Individual ET responses to water scarcity have been noted in many Mediterranean countries; for example, a simulation study by Malkia and Etsouri (2018) pointed out a three‐ to fivefold increase in agricultural water requirements in Algeria's Bounamoussa Perimeter irrigation scheme, which is one of the larger irrigation systems in the north‐east of Algeria. Similarly, Herrera et al (2015), using climate forecasting, found that Spain will experience a drop in annual precipitation as high as 30%, and an 18% increase in potential ET in the next few decades.…”
Section: Introductionmentioning
confidence: 99%